2023
DOI: 10.3389/fmed.2023.1202504
|View full text |Cite
|
Sign up to set email alerts
|

Corticosteroids in COVID-19: pros and cons

Aymen Bahsoun,
Yeva Fakih,
Rana Zareef
et al.

Abstract: The wide and rapid spread of the COVID-19 pandemic has placed an unanticipated burden on the global healthcare sector. This necessitated a swift response from the international community to reach a solution. Efforts were made in parallel to develop preventative and therapeutic modalities. Since then, drug repurposing has blossomed as a potentially rapid resolution and has included various agents with anti-viral and anti-inflammatory properties. Corticosteroids, being potent anti-inflammatory agents, have been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 107 publications
0
11
0
Order By: Relevance
“…Therapeutic steroid use in COVID-19 is a huge and extensively studied issue of the pandemic. Downregulation of a pathogenic cytokine storm was discussed as beneficial in certain subgroups during acute COVID-19 [ 59 ]. Nevertheless, chronic steroid use—which means pre -existing to SARS-CoV-2 infection—was associated with symptomatic disease and risk for a severe course of COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…Therapeutic steroid use in COVID-19 is a huge and extensively studied issue of the pandemic. Downregulation of a pathogenic cytokine storm was discussed as beneficial in certain subgroups during acute COVID-19 [ 59 ]. Nevertheless, chronic steroid use—which means pre -existing to SARS-CoV-2 infection—was associated with symptomatic disease and risk for a severe course of COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, some medications can affect heart muscle function, e.g., corticosteroids affecting muscle metabolism and inflammation. Several studies have found a negative impact of long‐term high‐dose corticosteroid therapy during COVID‐19 on the occurrence of, among others, myocardial infarction, bacterial sepsis, cerebrovascular and ophthalmological diseases 44–47 . Similarly, Remdesivir potentially affects cardiac repolarisation 48 .…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have found a negative impact of long-term high-dose corticosteroid therapy during COVID-19 on the occurrence of, among others, myocardial infarction, bacterial sepsis, cerebrovascular and ophthalmological diseases. [44][45][46][47] Similarly, Remdesivir potentially affects cardiac repolarisation. 48 Several studies have reported cardiovascular side effects of Remdesivir, including bradycardia, hypotension, QTc prolongation, nonspecific T wave changes, and cardiac arrest.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Steroids can be used in patients with COVID-19, who show progressive deterioration of oxygen saturation, increased activation of the pro-inflammatory response, and rapid worsening of features on chest imagining [30], [31]. Various trials have recorded the beneficial outcome of corticosteroids in decreasing the mortality and morbidity of COVID-19 [32]. In the context of a severe COVID-19 case, where the infection has not been cleared by the initial immune response and has entered the pulmonary phase, the proposed benefit of the introduction of corticosteroids is thought to be due to the downregulation of immune-mediated lung injury and cytokine storm [18].…”
Section: Case 2 (Aa)mentioning
confidence: 99%